Hubungan Dukungan Keluarga Dan Efikasi Diri Terhadap Kepatuhan Asupan Cairan Pada Pasien Gagal Ginjal Kronik Diruang Hemodialisa RSI Purwokerto - Risang Sukma Wahyu Nurlaela; Nur Isnaini (Jurnal Keperawatan Muhammadiyah, 2020)
Background: Chronic kidney disease is a progressive clinical syndrome of decreased kidney function that is irreversible. Patients with chronic renal failure (GGK) undergoing hemodialysis therapy are suggested to limit and regulate their daily fluid intake. However, this suggestion demands patients' compliance. Objective: To find out the correlation between family support and self-efficacy with adherence to fluid intake in patients with chronic kidney failure in the hemodialysis room at RSI Purwokerto. Method: This is a quantitative descriptive with a cross-sectional approach. There were 48 respondents taken as the research sampling done by Total Sampling in accordance with the inclusion and exclusion criteria applied. The research instrument used questionnaire sheets analyzed using Pearson Product Moment test. Results: Most respondents, 18 patients (37.5%), were 46-55 years old, 28 patients (28.3%) were female, 44 patients (91.7%) were married, 21 patients (43.8%) were graduated from primary school, and 33 patients (68.8%) did not work. Most respondents, 24 patients (50.0%), had sufficient family support to support and 27 patients (56.2%) had a medium level of self-efficacy with the highest frequency. Pearson correlation test results obtained family support variable p-value of 0,000 and r count (0.672) r table (0.285), then self-efficacy variables obtained p-value of 0,000 and r count (0, 658) r table (0.285).Conclusion: There is a correlation between family support and self-efficacy with adherence to fluid intake in patients with chronic renal failure in the hemodialysis room at RSI Purwokerto.